Dynamic responses and energy absorption of hollow sphere structure subjected to blast loading. (5th November 2019) - Tang, Fan; Sun, Yanlong; Guo, Zerong; Chen, Wensu; Yuan, Mengqi
Abstract: Closed-cell and open-cell hollow spheres were designed to develop lightweight cellular structures with excellent blast resistance, and the mechanical response of the hollow sphere structure (HSS) under blast loading was investigated numerically using ANSYS®/LS-DYNA®17.0. In this paper, the blast wave pressure decay rate was served as the main index of blast resistance while areal specific energy absorption and frame deformation were used as auxiliary indexes. The results indicated that the weight of HSS was reduced by 37.7%–69.8% compared to solid structures with the same physical size, and the blast resistance of HSS was significantly affected by the hollow sphere diameter and wall thickness, frame length and width, opening size and opening density. Closed-cell HSS with smaller hollow sphere diameters and thicker wall, or smaller frame lengths and widths would achieve the optimal blast resistance. Meanwhile, the blast resistance of HSS could be improved by adopting a smaller opening size, but the effect of opening density did not follow any rule, which was affected by the number and position of openings. Comprehensively, the blast resistance of HSS was enhanced when there was opening only at the face blast surface rather than at both the face blast surface and back blast surface. Graphical abstract: Unlabelled Image Highlights: Lightweight hollow sphere structure was designed to reduce the weight by 37.7%~69.8%. Parametric study was carried out to improve the blast resistance of hollow sphere structure. The open-celled hollow sphere structure exhibited better blast resistance than the closed-cell hollow sphere structure. Blast-proof mechanism and blast resistance of hollow sphere structure was identified.